A new long-legged terrestrial freshwater crab, Calcipotamon puglabrum gen. nov. et sp. nov. (Crustacea: Decapoda: Potamidae), from Hainan Island, China - Huang, Chao; Huang, Sheng-Zhuo; Shen, Zhi-Xin (Zootaxa, 2020)
A new genus and new species of terrestrial freshwater crab, Calcipotamon puglabrum gen. nov. et sp. nov., is described from the limestone forests of Changjiang, Hainan Island, China, based on morphology and mitochondrial 16S rDNA sequences. The new genus is closest to Neotiwaripotamon Dai & Naiyanetr, 1994, and Tiwaripotamon Bott, 1970, but differs in a combination of carapace, third maxilliped, ambulatory leg and male gonopod characters. Molecular analysis shows that the new genus is closely related with but not clustered within other Hainan potamid genera. Notes on the general biology of this new species are also provided.